(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
The article analyzes the impact of the Soviet tax and compulsory payment policy on the socio-economic life of the rural population of the Kashkadarya region in 1941–1945. The increase in the tax burden, the compulsory transfer of agricultural products, and the policy of state procurement prices are considered. The incomes of collective farmers based on labor and changes in food supply are analyzed. The social consequences of the widespread involvement of women in agricultural production in conditions of labor shortage are highlighted. The impact of wartime fiscal policy on the real incomes of the rural population, labor incentives, and economic stability is based.